Pengaruh Penggunaan Smartphone Terhadap Tingkat Efektifitas Belajar Siswa MTs Anwar Futuhiyyah - Fatmawati, Fifi; Kurnia, Heri (CV. Kurnia Grup, 2025)
This study aims to determine the effect of smartphone use on student learning effectiveness at MTS Anwar Futuhiyyah. The method used is a quantitative method with a simple linear regression approach. The results of the hypothesis test indicate that there is no significant effect between smartphone use (variable X) on student learning effectiveness (variable Y). This is proven through regression analysis with the equation Y = 52.806 + 0.043X, where the X coefficient is 0.043 and the constant is 52.806. The correlation coefficient (R) value of 0.002 indicates a very weak relationship between the two variables. Meanwhile, the R Square value of 0.002 or 0.2% indicates that only 0.2% of the variation in learning effectiveness can be explained by the smartphone use variable, while the other 99.8% is influenced by other factors not analyzed in this study. Thus, smartphone use does not have a significant effect on student learning effectiveness.